Aquatic plants govern CH4 and CO2 production and flux partitioning in lake emission pathways - Yue Geng; Ruihong Yu; Xixi Lu; Xiangwei Li; Xiaozhuang Wang; Yiming Zhao; Quanzhi Liu; Heyang Sun; Rui Wang (Ecological Indicators, 2025)
Shallow lakes are major contributors to atmospheric CH4 and CO2 emissions. However, limited research has systematically assessed the three primary emission pathways, diffusion, ebullition, and plant-mediated transport, across heterogeneous lacustrine habitats within these ecosystems. This study combined field surveys and gas stable carbon isotopic analyses to quantify CH4 and CO2 emissions through multiple pathways (diffusion, ebullition, and plant-mediated) in different habitats, including open water (OW), emergent vegetation (E), submerged vegetation (S), and submerged and macrofilamentous algal symbiosis (SA), in Lake Ulansuhai during the growing season. Compared with the remaining three habitats, habitat SA had the highest CH4 emission (17.41 ± 20.65mmol m−2 d−1) and the lowest CO2 emission (50.27 ± 40.03mmol m−2 d−1). CH4 emissions peaked during the peak growth season in July, whereas CO2 emissions peaked at the end of the growing season in October. The vegetated habitats had nine times more CH4 than the non-vegetated habitats. The CH4 flux from the vegetated habitats was primarily plant-mediated (mean 74 %), followed by ebullition (17 %). The fractionation factor (αC) values of δ13C-CH4 and δ13C-CO2 in the dissolved gas and bubbles indicated more acetoclastic methanogenesis, with CO2 likely derived from organic matter remineralization and biometabolism. This indicates that the plants promoted methanogenesis by providing substrates, contributing to the high CH4 emissions from Lake Ulansuhai. This study improves the accuracy of regional carbon emission estimates in multi-habitat aquatic systems and further elucidates how aquatic plants influence carbon emissions.